Повышение окислительной стойкости СОТС растительной природы присадками из антиоксидантов - Менумеров, Э. Р.; Якубов, Ч. Ф.; Аметов, И. Э. (НТУ "ХПІ", 2009)
The opportunity of increase of oxidizing stability of vegetable oils is considered with the help antioxidants. The choice optimum antioxidant for metal working fluids is made on the basis of vegetable oils. In research was used antioxidant alpha-tocopherol. Also practically is proved necessary and sufficient quantity anti-oxidantins unflower oil, as basic oil for metal working fluids.
Keywords: растительные масла; окислительная стойкость; генная инженерия; термоокислительная дистукция